Monetary-fiscal policy interactions in the euro area (European Central Bank (ECB), 2021)
The last review of the ECB's monetary policy strategy in 2003 followed a period of predominantly upside risks to price stability. Experience following the 2008 financial crisis has focused renewed attention on the question of how monetary and fiscal policy should best interact, in particular in an environment of structurally low interest rates and persistent downside risks to price stability. This debate has been further intensified by the economic impact of the coronavirus (COVID-19) pandemic. In the euro area, the unique architecture of a monetary union consisting of sovereign Member States, with cross-country heterogeneities and weaknesses in its overall construction, poses important challenges. Against this background, this report revisits monetary-fiscal policy interactions in the euro area from a monetary policy perspective and with a focus on the ramifications for price stability and maintaining central bank independence and credibility. The report consists of three parts. The first chapter presents a conceptual framework for thinking about monetary-fiscal policy interactions, thereby setting the stage for a discussion of specifically euro area aspects and challenges in subsequent parts of the report. In particular, it reviews the main ingredients of the pre-global financial crisis consensus on monetary-fiscal policy interactions and addresses significant new insights and refinements which have gained prominence since 2003. In doing so, the chapter distinguishes between general conceptual aspects - i.e. those aspects that pertain to an environment characterised by a single central bank and a single fiscal authority and those aspects that pertain to an environment characterised by a single central bank and many fiscal authorities (a multi-country monetary union). ...
Keywords: E52; E58; E62; E63; F45; 330; Monetary Policy; Fiscal Policy; Monetary Union